Internet connectivity disruption in Bulgaria (Bulgaria) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Bulgaria. Data sourced from IODA.
Network Disruption Incident ID: BG-2026-0026. Severity: critical. Confidence: 65%